Cluster Analysis of Patients’ Clinical Information for Medical Practitioners and Insurance Companies - Memon, Qurban A; Hassan, Mohammad E (International Journal of Online and Biomedical Engineering (iJOE), 2020)
A number of approaches have been proposed in literature to collect and classify patient related information for purpose of better clinical diagnosis and thus safer treatment and administration of related activities. This type of data collection and classification benefits doctors and the corresponding hospitals. However, no effort is made, as to our knowledge, to classify accumulated data within insurance company databases to facilitate doctors as well as insurance companies for better analysis and cost-effective treatment of patients suffering from chronic (and expensive to treat) diseases such as related to oncology. In this study, a customized self-organized data classification model is applied to an insurance company database to build clusters based on age, patient condition, tests done, etc. These clusters provide integrated analysis to doctors in providing patient-specific, disease-specific, etc., and thus cost-effective treatment. On the other side, it saves on costs to be incurred on repeated tests to be done on the patient. An experimental setup is developed to train such a network, and testing results are presented. The practical constraints are also discussed.